High prevalence of intestinal schistosomiasis in school-age children in the villages adjacent to Lake Chamo in the southern Rift Valley of Ethiopia. - Yenenesh Ayele; Teklu Wegayehu; Daniel Woldeyes; Fekadu Massebo (Public Library of Science (PLoS), 2024)
Background The prevalence of intestinal schistosomiasis remains a challenge despite government efforts to eliminate the disease. This study aims to assess the prevalence of intestinal schistosomiasis in school-age children living in the villages surrounding Lake Chamo in southern Rift Valley of Ethiopia. Methodology/principal findings A cross-sectional study was conducted from January to July 2023 in Shele Mela Kebele in Gamo Zone, South Ethiopia. Stool samples were collected from 597 school-age children. A singe Kato-Katz for helminths and formalin-ether concentration technique for protozoan parasites were used to process the samples. The intensity of Schistosoma mansoni infection among school-age children was determined by counting the number of eggs per gram of stool. Of the 597 children screened, 52.3% (95% CI: 48.4.4-56.4) were positive for Schistosoma mansoni. These findings showed that 55% of the infections were light, 30.3% were moderate, and 14.7% were heavy. The mean egg count of S. mansoni parasites was 182.1 eggs per gram. The prevalence of other intestinal parasites (Hymenolopis nana, Ascaris lumbricoides, Hookworm, Taenia species, Giardia lamblia and Entamoeba histolytica) was found to be 7.7% (46/597). The overall prevalence of S. mansoni co-infection with other intestinal parasites was 5.0% (30/597). Specifically, the co-infection rates were 1.5% for A. lumbricoides, 1.3% for H. nana, 1.0% for Taenia species, 0.2% for Hookworm, 0.2% for E. histolytica, and 0.2% for G. lamblia. Conclusions/significances The study showed a high rate of S. mansoni infection among school-age children. This calls for immediate action, such as school-based deworming, to protect these children from the disease and reduce the burden. Further research is needed to understand the transmission of the infection by the intermediate host.